Understanding the impact of cloud-based services adoption on organizational flexibility: An exploratory study. Issue 4 (11th July 2016) - Lal, Prerna; Bharadwaj, Sangeeta Shah
Abstract : Purpose: – The purpose of this paper is to explore the factors that drive the adoption of cloud-based services and further understand the impact of this adoption on the organizational flexibility. This study presents information technology executive's perspective and discovers new constructs of organizational flexibility that can be achieved due to the adoption of cloud-based services, which is the main contribution of this paper. Design/methodology/approach: – This study uses in-depth interview approach. Total 21 Indian cases were studied by interacting with respondents having similar profiles (i.e. CIOs, CTOs, technology heads, and systems managers). Based on the literature review a semi-structured questionnaire was prepared and administered through in-depth interviews. Findings: – Analysis of data reveals that cloud-based services provide relative advantage in terms of scalability, accessibility, and on-demand deployment of services within no time. Easy to use interface, experience, and expertise of the cloud service provider as well as support from top management plays important role in the cloud adoption decision. Further the study also identifies that no matter which model of cloud-based services (software-as-a-service (SaaS), platform-as-a-service (PaaS), or infrastructure-as-a-service (IaaS)) is used; cloud-based services' adoption impacts organizational flexibility, which can be divided into four categories, namely, economic flexibility, process flexibility, performance flexibility, and market flexibility. Research limitations/implications: – This is an exploratory study conducted through in-depth interviews hence the results can further be verified through a quantitative research. The study does not explore negative factors that may discourage adoption of cloud-based services. Though two factors vendor lock-in and security emerged as a concern very prominently in the in-depth interviews but this issue can further be explored in detail. Originality/value: – This study bridge the gap in the research by identifying the factors that drive the adoption of cloud-based services in different forms (SaaS, PaaS, and IaaS) as well exploring the impact of cloud adoption on the organizational flexibility in case of Indian organizations.